Facile Synthesis of Cross-linked Hyperbranched Polyamidoamines Dendrimers for Efficient Hg(Ⅱ) Removal From Water - Geng, Xue; Qu, Rongjun; Kong, Xiangyu; Geng, Shengnan; Zhang, Ying; Sun, Changmei; Ji, Chunnuan (Frontiers in Chemistry, 2021)
Dendrimers as commonly used metal ions adsorption materials have the advantages of good adsorption performance and high reuse rate, but the high cost limits its extensive use. Compared with dendrimers, hyperbranched dendrimers have similar physical and chemical properties and are more economical. Therefore, hyperbranched dendrimers are more suitable for industrial large-scale adsorption. The hyperbranched polyamidoamine (HPAMAM) gels were prepared by cross-linking hyperbranched polyamidoamine (HPAMAM-ECH-x and HPAMMA-EGDE-x) with different amounts of epichlorohydrin (ECH) and ethylene glycol glycidyl ether (EGDE), respectively. The as-synthesized adsorbents were characterized by FT-IR, SEM and XPS. The prepared adsorbents were used to adsorb Hg(Ⅱ) in aqueous solution, and the effects of solution pH, contact time, temperature and initial concentration of metal ion on the adsorption capacity were investigated. The effect of solution pH indicated that the optimum condition to Hg(Ⅱ) removing is at pH 5.0. The adsorption kinetic curves of the two kinds of materials were in accordance with the pseudo-second-order model. For the HPAMMA-ECH samples, the adsorption thermodynamic curves fitted the Langmuir model, while for the HPAMMA-EGDE samples, both Langmuir and Freundlich equations fitted well. The maximum adsorption capacity of HPAMAM-ECH-3 obtained from Langmuir model toward Hg(Ⅱ) was 3.36 mmol/g at pH 5.0 and 35 ℃.